The Interplay of Political Philosophy and Doctrine in Ismaili Thought - Alhassani , Hawraa (Al-Adab Journal, 2024)
The research presents an insightful perspective on the relationship between faith and politics within the Ismaili Shiite sect of Islam. It highlights the distortions and misrepresentations that Ismailism has faced from various groups, including hostile Sunni and Shiite Islamists, as well as Western Orientalists and Crusaders. The research aims to shed light on the interconnectedness between the religious and worldly aspects of Ismailism, particularly the concept of the Imamate, which is seen as a theory of religious message and worldly leadership.The research suggests that much of the distortion surrounding Ismailism is rooted in political and religious interference, where Muslims accused Ismailis of infidelity and distorted their faith for political reasons. Similarly, Orientalists and Crusaders are accused of recreating and misrepresenting the image of Ismailis in the Western imagination, fueled by myths, tales, and hostile imaginations stemming from the Ismailis' opposition to both the Crusaders and the Tatars.Interestingly, the abstract draws a connection between these fantasies about Ismailis and contemporary terrorism, suggesting that there is an attempt to link Ismailism with terrorism in a continuation of the historical hostilities against this sect.The research effectively sets the stage for a comprehensive exploration of the interplay between faith and politics within Ismailism, while also highlighting the need to confront the distortions and misrepresentations that have plagued this sect throughout history.